Co‐expression of HLA‐B7 and HLA‐B27 alleles is associated with B7‐restricted immunodominant responses following influenza infection. (20th October 2013) - Akram, Ali; Inman, Robert D.
<x xml:space="preserve">Abstract</x> It is recognized that host response following viral infection is characterized by immunodominance, but deciphering the different factors contributing to immunodominance has proved a challenge due to concurrent expression of multiple MHC class I alleles. To address this, we generated H2‐K−/−/D−/− double‐knockout transgenic mice expressing either one or two human MHC‐I alleles. We hypothesized that co‐expression of different allele combinations figures critically in immunodominance and examined this in influenza‐infected, double Tg MHC‐I mice. In A2/B7 or A2/B27 mice, using ELISpot assays with the A2‐restricted matrix I.58–66, the B7‐restricted NP418–426 or the B27‐restricted NP383–391 influenza A (flu) epitopes, we observed the expected recognition of both peptides for both alleles. In contrast, in flu‐infected B7/B27 mice, a significantly reduced level of B27/NP383‐restricted CTL response was detected while there was no change in the B7/NP418‐restricted CTL response. Flu‐specific tetramer studies revealed a partial deletion of Vβ8.1+ NP383/B27‐restricted CD8+ T cells, and a diminished Vβ12+ CD8+ T‐cell expansion in B7/B27 Tg mice. Using HLA Tg chimeric mice, we confirmed these findings. These findings shed light on the immune consequences of co‐dominant expression of MHC‐I alleles for host immune response to pathogens.